Associations between nine dietary minerals intake and all-cause mortality in individuals with atherosclerotic cardiovascular disease - Duan, Chenglin; Lv, Meng; Shou, Xintian; Chen, Zizhen; Luan, Yujie; Hu, Yuanhui (Frontiers in Nutrition, 2024)
Background: Varied intake of dietary minerals critically affects cardiovascular health. This study examines the associations of nine dietary minerals intake with all-cause mortality in atherosclerotic cardiovascular diseases (ASCVD). Methods: This study analyzed 4,125 individuals with ASCVD from National Health and Nutrition Examination Survey, employing Kaplan-Meier survival analyses, weighted Cox models, and restricted cubic splines to assess linear and nonlinear relationships between dietary minerals intake and all-cause mortality. Associations across different body mass index (BMI) categories were also evaluated separately. Results: Over 6.25 years of median follow-up, 1,582 deaths were documented. Adjusted for potential covariates, results show a negative linear correlation between dietary magnesium intake and all-cause mortality (p for trend < 0.001). Compared to the lowest quartile, all-cause mortality risk in the highest quartile was found to be 0.63 (95% CI 0.49-0.81). The associations between intake of the other eight dietary minerals and all-cause mortality were not robust. BMI significantly influenced the links between dietary minerals intake and all-cause mortality (p for interaction < 0.05). Across BMI categories, significant negative associations were found between intake of magnesium, phosphorus, potassium, sodium, and copper and all-cause mortality in underweight or normal weight groups. In overweight individuals, intake of calcium, iron, magnesium, and potassium was negatively linked to all-cause mortality. For obese groups, sodium intake negatively affected all-cause mortality (p for trend < 0.001). Conclusions: Unlike other dietary minerals, increased magnesium intake significantly reduced all-cause mortality risk in ASCVD. BMI influenced the associations between dietary minerals intake and all-cause mortality.